A Study on the Causes and Effects of Audit Failure -- a Case of Dahua Accounting Firm’s Jintongling - Hou Bohan (SHS Web of Conferences)
As an important regulatory force in the capital market, the audit quality of accounting firms has a direct impact on market order and investor rights. However, in recent years, frequent audit failures have exposed deep-seated problems in the industry. This paper takes Dahua Accounting Firm’s audit failure case involving Jintongling as the research object and uses qualitative research method to deeply analyze the causes and effects of audit failure. This paper has found that the three factors of insufficient professional quality of auditors, ineffective on-site inventory observation, and failure to effectively identify and manage fraud risks constitute a transmission chain of “capability deficiency - procedure failure - risk out of control”, which are the main causes of audit failure; The effects of audit failure manifests as a triple crisis of business decline, talent loss, and market position collapse. This will seriously damage its reputation accumulated over the years in the industry, and its future development will also face numerous obstacles.